Analyses of exon 4a structure reveal the properties of Big tau related to distribution, function and aggregation - Fischer, Itzhak; Baas, Peter W. (Frontiers in Molecular Neuroscience, 2025)
Tau, a microtubule-associated protein that modulates the dynamic properties of microtubules, is best known for its involvement in tauopathies. Usually expressed as the low molecular (LMW) variants of 45–60 kDa, tau is also expressed as a high molecular weight isoform of 110 kDa, termed Big tau, in neurons of the peripheral nervous system and in a few types of central neurons. Big tau is defined by the inclusion of exon 4a, which adds about 250 amino acids to the projection domain. Despite low sequence conservation the length of the Big tau insert remains remarkably consistent across vertebrates. Here, we analyzed the charge distribution, hydrophobicity, and aggregation propensity of the human sequences of LMW tau, Big tau and the amino acids encoded by exon 4a. Exon 4a amino acids display a pronounced negative net charge of acidic amino acids, an overall hydrophilic composition and low β-sheet content. This contrasts with LMW tau, which is more hydrophobic with extended aggregation-prone motifs including a relatively high β-sheet content. Inclusion of exon 4a in Big tau shifts the global hydrophobicity to intermediate values and reduces predicted β-sheet content, suggesting decreased aggregation propensity. We propose a model in which inclusion of the additional stretch of amino acids encoded by exon 4a shields the aggregation motifs of LMW tau and limits their exposure, which together with its unique biophysical structure, defines the properties of Big tau, Evolutionary analyses across vertebrates (human, rat, zebra finch, frog) confirms the minimal sequence identity and conserved exon size but shows preservation of negative net charge indicating convergent retention of charge-based properties. Hydrophilicity was also broadly conserved, though less invariant across species. These results are consistent with the presence of Big tau in neurons that are resistant to tauopathies that commonly afflict neurons expressing only LMW tau.